Development of Non-sticking Steady-State solution for structures with hybrid damping mechanism. (January 2023) - Ziaee, Mohammad; Hejazi, Farzad
Abstract: Energy dissipation occurs through Coulomb friction and is considered a conventional type of mechanical damping mechanism in structures subjected to external loads. Structures that are subjected to severe dynamic excitations such as ground motion or wind are required to employ a supplementary dampening system in addition to the Coulomb damping to mitigate the adverse impact of vibration in structures. Therefore, this study aims to develop a new Hybrid Damping Mechanism (HDM) for a single-degree-of-freedom (SDOF) system which is subjected to harmonic loads through a Viscous Damper System (VDS) to enhance the energy dissipation efficiency besides the Coulomb friction. Therefore, an analytical dynamic model for the non-sticking steady-state response was formulated where the effects of the viscous damper were implemented in the governor equation of the motion to estimate the structural response under harmonic loads. Subsequently, the Maximum Displacement (MD) and the Maximum Velocity (MV) were estimated by assuming deviation from the equilibrium point. Finally, a genuine borderline equation and a boundary limit were derived for the force amplitude ratio, where the maximum external load was divided by kinetic friction. It is an appropriate guideline for structural designers to avoid the sticking phase in the dynamical analysis of the structural systems equipped with frictional dampers. Based on the application of the final solution to a numerical example, the proposed HDM in the SDOF system considerably diminished the MD with velocity deviation ranging between 5% and 98% and 3% to 94%, respectively. Meanwhile, the analysis also revealed that the VDS damping ratio and the force amplitude ratio were the most effective parameters in reducing the MD and velocity deviation with a frequency ratio ( β ) between 0.85 and 1.15. The developed hybridized SDOF system can also be applied as a Tuned Mass Damper (TMD) in the structures to ameliorate their dynamic response.